An integrated approach to the Superplastic Forming of lightweight alloys: towards sustainable manufacturing. (3rd July 2008) - Abu-Farha, Fadi K.; Khraisheh, Marwan K.
This paper brings to light the sustainability aspects of forming lightweight materials using the superplastic forming technique, emphasising the long-term potentials in reducing the adverse impact of the transportation industry on the environment. This is carried out by a qualitative sustainability assessment of both process and material, with regard to the various elements of the comprehensive 6R approach. And in an effort to further refine and enhance its sustainability role, a comprehensive integrated approach to the superplastic forming of lightweight materials is presented. This approach uniquely accounts for and blends the process/material interaction on the pre-forming, forming and post-forming levels.